Elementi peculiari della dottrina spirituale di Caterina da Siena - Tagliafico, Angela (Alpha Omega, 2014)
Summary: The main themes of the spiritual doctrine of St. Catherine of Siena, doctor of the Church, as they emerge from her works, Dialogue with Divine Providence, Prayers and Letters, are the following: her eminent Christocentrism which appears in her doctrine of Christ as the bridge and in the exaltation of the blood of Christ, her vision of the Church founded in the blood of Christ, bride of the Trinity in Christ, the importance she attributes to the knowledge of self which human beings are called to realise in order to undertake the right spiritual journey which leads them to union with God, the value of discretion which for her emerges from that human knowledge of self which unites the vision of God with the vision of the human being, from which charity arises and, finally, the theme of prayer, which, for Catherine, represents above all the ardent desire of the love which moves and guides every expression of persons who aim to allow themselves to be drawn by God into that profound and deep sea which is He Himself, Love in its essence.